UiTM sustainability initiatives, challenges and way forward - UiTM, UGC (UiTM Green Centre, 2025)
SHAH ALAM, OCTOBER 16, 2025 - Sharing session with Japan students on ‘UiTM Sustainability Initiatives, Challenges and Way forward’ for Toyo University, Japan - UiTM, Malaysia In-bound student mobility programme. Delivered by Sr Dr Wan Samsul (UGC Deputy Director and Dr Che Bon Ahmad (Coordinator, Communication & Industry Linkages, UGC). Programme PiC department of building surveying, Faculty of Built Environment UITM Shah Alam).